Desymmetrization of a Propane-1,3-diol to Introduce the Quaternary Chiral Center of an AMG 176 Drug Substance Intermediate - Ananthoji, Padmini K.; Arunachalampillai, Athimoolam; Beaver, Matthew G.; Fang, Yuan-Qing; Hedley, Simon J.; Lucas, Brian S.; Tedrow, Jason S.; Faul, Margaret M. (Synthesis, 2023)
A chiral Cu(II)-PyBOX complex was prepared and utilized to accomplish desymmetrization of a 1,3-diol en route to AMG 176. An expedient synthesis of the racemic 1,3-diol is described, in addition to efforts for rapid optimization and subsequent kilogram-scale execution of the desymmetrization process to generate material for pre-clinical activities. An overview of the kilogram-scale synthesis of the Cu(II)-PyBOX complex is provided.
Keywords: AMG 176; process development; desymmetrization; Evans; PyBOX ligand; 1,3-diol